The cancer-testis antigen a-kinase anchor protein 3 facilitates breast cancer progression via activation of the PTEN/PI3K/AKT/mTOR signaling. Issue 4 (1st April 2022) - Zhan, Chuan-Hua; Ding, Dong-Shen; Zhang, Wei; Wang, Hong-Liang; Mao, Zhe-Yu; Liu, Guo-Jun
ABSTRACT: The cancer-testis antigen A-kinase anchor protein 3 (AKAP3) has been shown to have a strong association with breast cancer (BC). However, its role in BC progression received scant attention. We aimed to explore the prognostic implication of aberrant AKAP3 expression for a better knowledge of BC progression and improved treatment. AKAP3 expression was quantitated using tissue microarrays and immunohistochemistry (IHC). Cell viability, invasion, migration, apoptosis, and expressions of PTEN/PI3K/AKT/mTOR signaling components were assessed in AKAP3-overexpressed or si-AKAP3-transfected BC cells. Finally, elevated AKAP3 expression was observed in BC versus paracancerous tissues. BC patients with high AKAP3 expression showed a worse prognosis than low expression patients ( P < 0.0001). AKAP3 overexpressions fueled cell growth, proliferation, migration, and invasion in HCC1937 and MDA-MB-468 BC cell lines, alongside increased expressions of PI3K/AKT/mTOR signaling components and PTEN suppression. These effects were pronouncedly reversed, together with elevated apoptosis, in cells transfected with si-AKAP3. Therefore, AKAP3 is upregulated in BC and promotes BC cell growth, invasion, and migration via PTEN/PI3K/AKT/mTOR signaling activation. It may serve as a prognosis indicator for BC survival. GRAPHICAL ABSTRACT: uf0001